1996
DOI: 10.1002/(sici)1097-010x(19960701)275:4<300::aid-jez8>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of bromodeoxyuridine in regenerating fin tissue of the goldfish Carassius auratus

Abstract: We have investigated the pattern of incorporation of 5-bromo-2'-deoxyuridine-5'-monophosphate (BrdU) by proliferating cells during regeneration of the tail fin of Carassius auratus. Fifteen days after amputation, intraperitoneal injection of a single dose of 0.25 mg/g wet weight of BrdU and subsequent immunocytochemical detection on sections revealed groups of replicating cells in the blastema and epidermis at different proximodistal levels. Proliferating blastemal cells were confined to a crowded, compact dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 0 publications
7
43
0
1
Order By: Relevance
“…However, recent investigations have demonstrated that it is possible to avoid these problems and successfully employ the BrdU methods by resorting to suitable short-term administrations (Oinuma et al 1992;Santamaría et al 1996). Our present and past results are consistent with these data and complete the view as far as the diverse possible applications of this method are concerned.…”
Section: Brdu Methodssupporting
confidence: 89%
“…However, recent investigations have demonstrated that it is possible to avoid these problems and successfully employ the BrdU methods by resorting to suitable short-term administrations (Oinuma et al 1992;Santamaría et al 1996). Our present and past results are consistent with these data and complete the view as far as the diverse possible applications of this method are concerned.…”
Section: Brdu Methodssupporting
confidence: 89%
“…This myosin isoform may permit the modification of the sarcomere structure providing a higher cellular plasticity that is needed for proliferation, migration and morphogenesis (Maggs et al, 2000). It is interesting to note that the cluster of embCMHC-expressing cells was confined to the distance of 100 μm from the injury site, which corresponds to the similar spatial domain that was reported for mesenchymal dedifferentiation during epimorphic fin regeneration (Akimenko et al, 2003;Poss et al, 2003;Santamaria et al, 1996). This correlation strongly suggests the existence of similar mechanisms and factors in both the fin and the heart, which spread from the injury site to promote cellular dedifferentiation of the abutting stump tissues.…”
Section: Discussionsupporting
confidence: 71%
“…1A, B). On the basis of their position, these cells could be identified as differentiating dermal bone-forming cells or scleroblasts (Santamaria et al 1996). Histological sections along the proximodistal axis of the ray and cross sections showed that hoxa11b-and hoxa13bexpressing cells were mesenchymal and located between actinotrichia and the basal layer of the epidermis (Fig.…”
Section: Resultsmentioning
confidence: 99%